Innovative Tool For Composite Machining In Aerospace Application - Mohamad Nizar, Luqman Haikal (Universiti Sains Malaysia, 2022)
The rise of demand for advance materials including CFRP has pose new challenges for manufacturers to ensure sufficient and timely supply of parts, especially for commercial aircraft industry. Machining CFRP panels into net shape require numerous processes such as drilling, trimming and facing, making it a time-consuming process, as machine needs to be stopped to accommodate tool change process. By combining multiple tools into a single tool bit, the tool change process could be eliminated, which effectively translate into lower cycle time of CFRP machining. Having a lower cycle time and higher machine efficiency helps manufacturers to cope with the demand from customers. Conducting research using combined tool bits with a feed rate range of 0.05-0.15mm/rev and rotational speed range of 2500-10000rpm allows further understanding on the responses obtained in the experiment. Introduction of coating layer onto the tool bit helps to boost the tool bit performance in terms of tool life and also quality of machined parts. The three objectives set for this research were met, whereby the set target of effect of machining parameters to the quality performance of CFRP panel has been successfully explored. Commercial aircraft industry may benefit from this research as the results obtained in positive in terms of machining quality, and surely has the potential of reducing the overall manufacturing cost.